A Turiasaurian (Dinosauria, Sauropoda) Tooth from the Pliensbachian Hasle Formation of Bornholm, Denmark, Shows an Early Jurassic Origin of the Turiasauria - Milàn, Jesper (2023)
Publisher Copyright: © 2023 by the authors. This research received no external funding. We are grateful to the amateur collector Mette Agersnap Grejsen Hofstedt, who found the tooth and brought it to our attention, and to Sten Lennart Jakobsen for providing photos of the tooth. We thank the two anonymous reviewers whose input greatly contributed to the article.